A practical approach of gene silencing in the haloarchaeon Haloferax volcanii using CRSPRi technology - Cerletti, Micaela (2023)
Laboratory practices (LP) as a didactic strategy involve a dynamic teaching-learningprocess. This allows students to perform psychomotor and social actions throughcollaborative work (experimental work), associate various sources of information togenerate new conceptions, and reinforce theoretical concepts (elaboration of a report).Based on this, in the Biology and Biochemistry of Microorganisms course, we developedthis LP to conceptualize gene silencing through the inactivation of a gene using interferenceRNA (RNAi). In recent years, the CRISPR-Cas system, which represents the adaptiveimmune system of bacteria and archaea, has been adapted to specifically silence genes(interference CRISPR, CRISPRi). The CRISPR-Cas system in Haloferax volcanii wasmodified for gene repression in plasmids or chromosomes. Studies conducted by ourresearch group have shown that the biosynthesis of carotenoid pigments in H. volcanii,among other processes, is regulated by the membrane protease LonB. The followingobjectives were proposed for the LP: a) generate a mutant strain with reduced expressionof the lonB gene in H. volcanii using CRISPRi; b) verify the silencing of the lonB usingWestern blot (WB); c) determine the effect of silencing on pigment synthesis and growthrate. The students were divided into groups and carried out protocols that allowed them totransform H. volcanii with three RNAi constructs, analyze the phenotype of the transformedcells, perform a WB with anti-Lon antibodies, monitor growth, and extract pigments andestimate their concentration in control and silenced strains as methods to determine thesilencing of lonB and its effect on physiology. Strains with reduced expression of the LonBprotease gene were obtained in H. volcanii with two of the constructs, confirming silencingthrough WB. On the other hand, it was determined that silencing led to an increase in pigment concentration and a decrease in growth rate. The obtained results were elaboratedand presented in a final report with a scientific paper format.